2004
DOI: 10.1007/s00020-002-1198-4
|View full text |Cite
|
Sign up to set email alerts
|

On Factorization of Trigonometric Polynomials

Abstract: We give a new proof of the operator version of the Fejér-Riesz Theorem using only ideas from elementary operator theory. As an outcome, an algorithm for computing the outer polynomials that appear in the Fejér-Riesz factorization is obtained. The extremal case, where the outer factorization is also * -outer, is examined in greater detail. The connection to Agler's model theory for families of operators is considered, and a set of families lying between the numerical radius contractions and ordinary contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 12 publications
0
57
0
Order By: Relevance
“…Namely, there is a polynomial q(z) = d l=0 q l z l with complex coefficients such that p(z) = |q(z)| 2 , ∀z ∈ T. This yields that any sum of square magnitudes of univariate polynomials can be represented as only one square magnitude of a polynomial. For the case of the multivariate polynomials, Dritschel [6] proved that any (strictly) positive Laurent polynomial on the n-torus T n can be represented as a sum of square magnitudes of polynomials. Calderon and Perpinsky [3] and Rudin [17] proved that it is not always true for the case the polynomial is nonnegative on the torus T n , n ≥ 2.…”
Section: Pythagoras Number Of (Complex) Multivariate Laurent Polynomimentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, there is a polynomial q(z) = d l=0 q l z l with complex coefficients such that p(z) = |q(z)| 2 , ∀z ∈ T. This yields that any sum of square magnitudes of univariate polynomials can be represented as only one square magnitude of a polynomial. For the case of the multivariate polynomials, Dritschel [6] proved that any (strictly) positive Laurent polynomial on the n-torus T n can be represented as a sum of square magnitudes of polynomials. Calderon and Perpinsky [3] and Rudin [17] proved that it is not always true for the case the polynomial is nonnegative on the torus T n , n ≥ 2.…”
Section: Pythagoras Number Of (Complex) Multivariate Laurent Polynomimentioning
confidence: 99%
“…A discussion on the Pythagoras number of (complex) Laurent polynomials positive on the n-torus is given in Sect. 6. The Laurent polynomials in that section are considered as sum of square magnitudes of complex-coefficient polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…Note that an alternative proof of Putinar's theorem for trigonometric polynomials, building on ideas of operator theory, can be found in [6], where it is shown that factorable trigonometric polynomials (i.e. those which can be expressed as sum-of-squares) are dense, and in particular, strictly positive polynomials are factorable.…”
Section: Now Definingmentioning
confidence: 99%
“…then Delsarte, Genin and Kamp have shown [3] that for a given degree k, This leads to a simple proof of the Matrix Fejér-Reisz factorization Theorem (Helson [13], Dritschel [5], McLean-Woerdeman [16], Geronimo-Lai [10]) which will be useful later.…”
Section: Is a Doubly Toeplitz Matrix If And Only Ifmentioning
confidence: 99%
“…As indicated above denotẽ 5) where the (n + 1) × (n + 1)(m + 1) matrixK n,m is given similarly to (3.4) with the roles of n and m interchanged. For the bivariate polynomials φ l n,m (z, w) above we define the reverse polynomials…”
Section: Bivariate Orthogonal Polynomialsmentioning
confidence: 99%